2020
DOI: 10.2528/pierl19101302
|View full text |Cite
|
Sign up to set email alerts
|

Gap-Coupled Dual-Band Evanescent-Mode Substrate Integrated Band-Pass Filter Waveguide

Abstract: A single-layer substrate integrated waveguide (SIW) is developed to design a dual-band band-pass filter (BPF) operating below the cutoff frequency of the SIW, known as evanescent-mode excitation. Gap-coupled excitation is used to demonstrate the multiple transmission poles (TPs) and transmission zeros (TZs) below the cutoff frequency of the SIW. The structure is reported to realize two independent evanescent-mode poles on a single-layer SIW which reduces the size and complexity of the structure compared to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Moreover, the SIWs are modelled in the propagation direction with a Π-network of the lumped-element circuit [32,33]. In addition to TP realisation, the two SIWs also realise two TZs that are modelled by two series L g -C g circuits in the transverse direction [13,14].…”
Section: Gap-coupled Discontinuitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the SIWs are modelled in the propagation direction with a Π-network of the lumped-element circuit [32,33]. In addition to TP realisation, the two SIWs also realise two TZs that are modelled by two series L g -C g circuits in the transverse direction [13,14].…”
Section: Gap-coupled Discontinuitymentioning
confidence: 99%
“…© 2022 The Authors. IET Communications published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology integrating auxiliary sub-structures, including bypassing couplings of non-resonating modes [6][7][8], side-wall cavities [9,10], mixed electric and magnetic couplings [11], and/or embedded irises [12][13][14][15]. Although these techniques are effective in TZ realisation, they all either add complexity to the design or increase the structure size.…”
Section: Introductionmentioning
confidence: 99%
“…the coupling between nonadjacent cavities or higher-order excitation are used for TZ realisation which results in the complicated and bulky 3D waveguide and/or SIW structures [19,20]. Recently, it has been shown that either the transmission poles (TPs) or TZs can be realised using metallic irises in the 3D waveguide and/or SIW structures [21,22]. The configurations and topologies of the metallic irises embedded in the 3D structure can be manipulated in such a way to realise TPs and/or TZs either above or below the 3D structure's cut-off frequency [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that either the transmission poles (TPs) or TZs can be realised using metallic irises in the 3D waveguide and/or SIW structures [21,22]. The configurations and topologies of the metallic irises embedded in the 3D structure can be manipulated in such a way to realise TPs and/or TZs either above or below the 3D structure's cut-off frequency [23,24]. In addition to cross-coupling between resonators, other studies have been reported in the literature related to TPs or TZs realisation [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A dual-mode dual-band bandpass filter using ridge gap structure is presented in [7], which needs only a single input and output. Many other types of single band [8][9][10][11] or dual-band [12] dual-mode filters have been studied in recent years.…”
Section: Introductionmentioning
confidence: 99%